Characterization of Physical Field and Flow Assurance Risk Analysis of Subsea Cage-Sleeve Throttling Valve - Jiang, Donglei; Meng, Wenbo; Huang, Yi; Yu, Yi; Zhou, Youwei; Jiang, Zhichen; Gao, Yonghai (Frontiers in Earth Science, 2021)
The subsea production system is presently widely adopted in deepwater oil and gas development. The throttling valve is the key piece of equipment of the subsea production system, controlling the safety of oil and gas production. There are many valves with serious throttling effect in the subsea X-tree, so the hydrate formation risk is relatively high. In this work, a 3D cage-sleeve throttling valve model was established by the numerical simulation method. The temperature and pressure field of the subsea throttling valve was accurately characterized under different prefilling pressure, throttling valve opening degree, and fluid production. During the well startup period, the temperature of the subsea pipeline is low. If the pressure difference between the two ends of the pipeline is large, the throttling effect is obvious, and low temperature will lead to hydrate formation and affect the choice of throttling valve material. Based on the analysis of simulation results, this study recommends that the prefilling pressure of the subsea pipe is 7–8 MPa, which can effectively reduce the influence of the throttling effect so that the downstream temperature can be kept above 0°C. At the same time, in regular production, a suitable choke size is opened to match the production, preventing the serious throttling effect from a small choke size. According to the API temperature rating table, the negative impact of local low temperature caused by the throttling effect on the temperature resistance of the pipe was considered, and the appropriate subsea X-tree manifold material was selected to ensure production safety. The hydrate phase equilibrium curve is used to estimate the hydrate formation risk under thermodynamic conditions. Hydrate inhibitors are injected to ensure downstream flow safety.